Nitric Oxide Controls Fat Deposition in Dystrophic Skeletal Muscle by Regulating Fibro-Adipogenic Precursor Differentiation. (17th March 2014) - Cordani, Nicoletta; Pisa, Viviana; Pozzi, Laura; Sciorati, Clara; Clementi, Emilio
Abstract: Duchenne muscular dystrophy (DMD) is an hereditary disease characterized by loss of muscle fibers and their progressive substitution by fat and fibrous tissue. Mesenchymal fibro-adipogenic progenitors (FAPs) expressing the platelet-derived growth factor receptor alpha (PDGFR α ) are an important source of fibrosis and adipogenesis in dystrophic skeletal muscle. Among the therapies suggested for dystrophy are those based on nitric oxide (NO) donating drugs, the administration of which slows disease progression. NO has been shown to act by enhancing the regenerative potential of the diseased muscle. Whether it acts also by inhibiting fibrosis and adipogenesis was not known. Here, we show in vitro that NO regulates FAP fate through inhibition of their differentiation into adipocytes. In mdx mice, an animal model of DMD, treatment with the NO donating drug molsidomine reduced the number of PDGFR α + cells as well as the deposition of both skeletal muscle fat and connective tissues. Inhibition of adipogenesis was due to NO-induced increased expression of miR-27b leading to downregulation of peroxisome proliferator-activated receptors gamma ( Pparγ1 ) expression in a pathway independent of cGMP generation. These findings reveal an additional effect of NO in dystrophic muscle that conceivably synergizes with its known effects on regeneration improvement and explain why NO-based therapies appear effective in the treatment of muscular dystrophy. Stem Cells 2014;32:874–885